Growth of food-borne pathogens Listeria and Salmonella and spore-forming Paenibacillus and Bacillus in commercial plant-based milk alternatives. (February 2023) - Bartula, Klaudia; Begley, Máire; Latour, Noémie; Callanan, Michael
Abstract: The objective of the present study was to compare the growth of food-pathogens Listeria monocytogenes, Salmonella enterica, food spoilage Bacillus subtilis, an industrial milk product isolate, and spore-forming Paenibacillus in commercially available ultrahigh temperature processed (UHT) bovine milk and non-dairy, plant-based beverages (coconut, almond, cashew) stored at chilled and ambient temperatures (4 °C, 8 °C or 20 °C). Beverage samples were inoculated with a strain cocktail or individual strains of either Listeria or Salmonella, or Paenibacillus or Bacillus, respectively (approximately 1 × 10 3  CFU/mL). The findings indicate that the bacterial strains used in the study were capable of proliferating in plant-based beverages at higher rates than in bovine milk at 8 °C and 20 °C for Listeria and 20 °C for Salmonella and Paenibacillus, respectively. Bacillus subtilis grew equally fast in bovine milk and plant-based almond drink at 20 °C. No statistically significant difference ( p  > 0.05) in growth rates between different types of tested beverages was observed at 4 °C and at 8 °C for Listeria and Salmonella cocktails, respectively. These data suggest that plant-based beverages may present a significant risk for listeriosis and salmonellosis and post-opening recommendations should be carefully considered. Highlights: Plant-based milk drinks support rapid growth of Listeria, Salmonella, Bacillus and Paenibacillus . Listeria grew significantly faster in plant-based beverages than in bovine milk at 8 °C and 20 °C. Salmonella growth rate was significantly higher in plant-based beverages than bovine milk at 20 °C. Growth of sporeformers was equivalent or faster in plant-based beverages than bovine milk at 20 °C.